Family functioning and aggressiveness in students of primary education of Puerto Maldonado: Funcionamiento familiar y agresividad en estudiantes de educación primaria de Puerto Maldonado - Estrada Araoz, Edwin Gustavo (2019)
Objective: To determine the relationship between family functioning and the aggressiveness of students in the sixth grade of primary education of the Alipio Ponce Vásquez Educational Institution of Puerto Maldonado. Materials and methods: Quantitative approach, non-experimental design and cross-sectional descriptive correlational type. The data collection technique was the survey and the instruments used were the Family Cohesion and Adaptability Assessment Scale (FACES III) and the AQ Aggression Questionnaire. Results: Spearman's rho correlation coefficient between family functioning and aggressiveness is -0.414 with a p-value below the level of significance (p= 0.002). Conclusions: There is a moderate, inverse and significant relationship between family functioning and aggressiveness. This means that as long as the students perceive a more adequate family functioning, the levels of aggression will be lower and vice versa. Keywords: Family relations; aggression; puberty (Source: MeSH, NLM).